LASER INDUCED PHOTO-ACOUSTIC SPECTROSCOPY FOR CANCER TISSUE OPTICAL ABSORPTION INVESTIGATION - Muhamad Hamdi; Usman Malik (Jurnal APTEK, 2014)
The ability to use with any incident radiation source makes this technique as an alternative way tostudy the absorption, scattering, molecular excitations, vibrations and defects in cancer cell tissue. Thispaper investigates the skin cancer cell tissue optical absorption in a range of infrared spectroscopy which isone of the main physical phenomena to effect on the phonon-photon radiation propagation from laserinduced photo-acoustic source. The main constituents of cancer cell tissue which contribute towardsabsorption in the near infrared are water, fat and hemoglobin. While the former two remain fairly constantover short time-scales, the concentrations of oxygenated and deoxygenated hemoglobin change according tothe function and metabolism of the cancer cell tissue. Thus the corresponding changes in cancer cell tissueoptical absorption can provide clinically useful physiological information.